2019
DOI: 10.7759/cureus.6466
|View full text |Cite
|
Sign up to set email alerts
|

Adaptogenic and Anxiolytic Effects of Ashwagandha Root Extract in Healthy Adults: A Double-blind, Randomized, Placebo-controlled Clinical Study

Abstract: Background Stress, anxiety and impeded sleep are a frequent feature of life in modern societies. Across socioeconomic strata, stress, anxiety and ineffective sleep detract from healthful living and serve as precursors of various ailments. The use of herbs to offset these antecedents and outcomes has greatly increased in recent years. Ashwagandha, an adaptogenic Ayurvedic herb, has been often used to combat and reduce stress and thereby enhance general wellbeing. While there have been other studies documenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
1
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(126 citation statements)
references
References 19 publications
3
93
1
3
Order By: Relevance
“…A root extract that warrants special attention is Withania somnifera (most known as ashwagandha) given some research have found ergogenic effects in athletic [ 121 , 122 ] and physically active individuals [ 123 ]. Moreover, the adaptogenic, anti-inflammatory, and antioxidant properties of ashwagandha [ 124 , 125 , 126 ] turns this herbal extract into a potential strategy to optimize recovery and promote exercise-induced adaptations. Although more research is required, dosages are between 300 and 500 mg of aqueous root extract twice per day.…”
Section: Resultsmentioning
confidence: 99%
“…A root extract that warrants special attention is Withania somnifera (most known as ashwagandha) given some research have found ergogenic effects in athletic [ 121 , 122 ] and physically active individuals [ 123 ]. Moreover, the adaptogenic, anti-inflammatory, and antioxidant properties of ashwagandha [ 124 , 125 , 126 ] turns this herbal extract into a potential strategy to optimize recovery and promote exercise-induced adaptations. Although more research is required, dosages are between 300 and 500 mg of aqueous root extract twice per day.…”
Section: Resultsmentioning
confidence: 99%
“…Tests on adult mice showed, that they achieve better results in swimming while they Ashagandha were supplemented. [3] At the beginning of the experiment, the animals withstood an average of 385 minutes while swimming, and after administering Ashwagandha, they withstood 740 minutes. A significant increase in swimming time indicates an increase in energy.…”
Section: The State Of Knowledge 21 Adaptogenic Propertiesmentioning
confidence: 99%
“…[4] In addition, Ashwagandha has been shown to reduce the levels of tribulin, a stress marker in the rat brain that was elevated by the administration of pentylenetetrozole. [3,4]…”
Section: The State Of Knowledge 21 Adaptogenic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tridoshara mainly Vatakaphahara, Sophahara, Balya, Vyadhinasana, Nidranasahara, Rasayana, Kasaswasahara. Researches proved that it has adaptogenic action, GABergic effect, serotogenric effect, phytoestrogenic effect, adrenal rejuvenating effect, Anxiolytic, cognitive enhancing effect, Cardiorespiratory endurant, mood stabilizer, sleep enhancing, memory booster, antiarthritic, antimicrobial, antiinflammatory effect [7] . Owing to these properties, Aswagandha choorna is highly beneficial in reducing physical, behavioural and psychological symptoms of PMS.…”
Section:  While Considering Aswagandha Choornam Ismentioning
confidence: 99%